Every day a Friday [compact disc, unabridged] : how to be happier 7 days a week - Osteen, Joel (Hachette Audio, 2011)
Known as a man who maintains a constant positive outlook in spite of circumstances, Pastor Joel Osteen has described this message as a core theme of his ministry. Combining his personal experiences with scriptural insights and principles for true happiness, he shows readers how every day can hold the same promise and opportunities for pure joy that they experience at five o'clock on Friday.